Antagonistic effect of selenium on lead-induced neutrophil apoptosis in chickens via miR-16-5p targeting of PiK3R1 and IGF1R. (May 2020) - Yin, Kai; Cui, Yuan; Sun, Tong; Qi, Xue; Zhang, Yue; Lin, Hongjin
Abstract: Environmental contamination by heavy metals, such as lead (Pb), can lead to severe immune dysfunction. MicroRNAs (miRNAs) are involved in regulating immunity. Whether Pb can regulate neutrophil apoptosis through miRNA, and whether selenium (Se) can antagonize this response are still unknown. We treated neutrophils with 12.5 μM (CH3 OO)2 Pb and 1 μM Na2 SeO3 for 3 h, after which apoptosis was evaluated using acrideine orange/ethidium bromide (AO/EB) dual fluorescent staining and flow cytometry. The results showed that neutrophil apoptosis was significantly increased following Pb exposure, and that this response was prevented upon Se addition. Pb up-regulates miR-16-5p and leads to the subsequent down-regulation of the target genes phosphoinositide-3-kinase regulatory subunit 1 (PiK3R1), insulin-like growth factor 1 receptor (IGF1R), and phosphatidylinositol 3 kinase (Pi3K)-protein kinase B (AKT), followed by activation of the tumor protein P53 (P53)–B-cell lymphoma-2 (Bcl-2)/Bcl-2-Associated X protein (Bax)-cytochrome c (Cytc)-Caspase 9 (mitochondrial apoptotic pathway) and the tumor necrosis factor receptor superfamily member 6 (Fas)-Fas-associated death domain protein (Fadd)-Caspase 8 (death receptor pathway). Pb also triggered oxidative stress and indirectly activated the mitochondrial apoptotic pathway. We conclude that miR-16-5p plays a key role in the apoptosis of neutrophils exposed to Pb by down-regulating the expression of PiK3R1 and IGFR1, thereby activating the mitochondrial apoptotic pathway and death receptor pathway. Se can prevent Pb-induced apoptosis. Graphical abstract: Image 1 Highlights: Lead inhibits the expression of IGF1R by up-regulating miR-16-5p, and then activates the death receptor pathway. Lead inhibits the expression of PiK3R1 by up-regulating miR-16-5p, and then activates the mitochondrial apoptosis pathway. Selenium can antagonize the toxicity of lead and prevent apoptosis.